Aβ‐potentiated and Aβ‐independent age‐related opacity changes in the lens of the eye in wild‐type and APPswe transgenic mice: Molecular and cell biology/APP/Abeta/amyloid. (7th December 2020) - Moncaster, Juliet A.; Minaeva, Olga; Goldstein, Lee E.
Abstract: Background: The lens of the eye is composed of crystallin proteins. These proteins have been shown to interact with Aβ in particular in Alzheimer's disease. Crystallin proteins undergo various post‐translational modifications during aging that disrupt the normal functioning of these proteins resulting in protein aggregation and light scattering. We expand on our previous work and investigated here the aging effect on lens opacity in an Aβ‐independent (wild‐type mice) and Aβ‐potentiated (Alzheimer's disease transgenic mice [APPswe]) environment. Method: Mice were bred, maintained and genotyped at Boston University. Mice were sacrificed at ages 8‐35 months, perfused with phosphate buffer saline, lenses were isolated and imaged under two different sources of light using a D70 digital Nikon camera and a Zeiss stereophotomicroscope. Result: Wild‐type aged mice demonstrated light scattering and opacities in two distinct regions of the lens in aged mice compared to younger mice. Moreover, APPswe aged mice showed increased scattering in the outer layer compared to wild‐type aged mice. Conclusion: Two distinct light scattering regions of the lens are affected during aging involving Aβ‐potentiated mechanisms in APPswe mice and Aβ‐independent mechanisms in wild‐type mice.